Innovation in Community Protection Against AI-Generated Content: Urgency of Applying Sunset Clause Method with Regulatory Impact Analysis Approach (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Dependence on Artificial Intelligence in helping to carry out daily tasks and activities is becoming increasingly significant. Various Artificial Intelligence services ranging from software development to foreign language translators have significantly increased the impact of Artificial Intelligence on society. However, the content produced by Artificial Intelligence can have major negative impacts, including the spread of disinformation through AI-Generated Content that threatens democracy and public trust, violations of privacy resulting from unauthorized use of personal data, discrimination, and prejudice. This study uses a normative legal research method with a legislative approach, a conceptual approach, and a comparative approach. This study shows that the Sunset Clause method in Indonesian law enforcement has great potential to increase the efficiency and relevance of laws and regulations in protecting society from the threat of the development of Artificial Intelligence technology, in line with SDGs point number 16 to ensure sustainable development in realizing the goals of the SDGs. This research provides innovation in the form of implementing the Sunset Clause model, which includes the validity period of a law, as well as a mechanism for reviewing laws and regulations through Regulatory Impact Analysis to protect the public from the threat of AI-Generated Content.